Making them talk: Examining students’willingness to communicate in an EMI class environment through instrumental motivation - Fielden Burns, Laura V.; Dorca Fornell, Carmen (Bibliotecas. Anales de investigación, 2021)
Objective: Communicative language teaching (CLT) is an approach that emphasizes an active interaction in the classroom, including the practice of productive skills like interactive speaking, a skill that is particularly important in EMI classes. In this paper, we evaluated the effect of a continuous evaluation system based on receiving points for speaking in the second language in class, which offered a more instrumental motivation, and its relationship to students’ perceived willingness to communicate (WTC) in affective, cognitive and behavioral components. Methodology. Once the points system was in place, it was used to encourage students to improve their fluency by participating in class in English, avoiding Spanish. When the course finished, a questionnaire examined their perceptions of the system and how it affected their English use in class. Results. Our results indicated a high percentage of students, 81%,who evaluated the system positively overall and who would want to continue it in the future, though lower levels of agreement were seen when looking at comfort and enjoyment. Finally, the qualitative results echo this data while offering more nuance on how the system affects students WTC. Conclusions: We conclude that the system was positive for students’ perceptions of their WTC, despite it being an instrumental motivation that looks toward a more extrinsic orientation. Originality. Our work explores the value of a positive reinforcement system that can push students to be more active about their foreign language use in class and explores an understudied area in foreign language teaching, instrumental motivation to improve students’ willingness to communicate. Objetivo: La enseñanza comunicativa del lenguaje (CLT) es un enfoque que enfatiza una interacción activa en el aula, incluida la práctica de habilidades productivas como el habla interactiva, una habilidad que es particularmente importante en las clases de EMI. En este trabajo evaluamos el efecto de un sistema de evaluación continua basado en la obtención de puntos por hablar en la segunda lengua en clase, que ofrecía una motivación más instrumental, y su relación con la disposición percibida para comunicarse (WTC) de los estudiantes en los aspectos afectivo, cognitivo y componentes conductuales. Metodología. Una vez que se implementó el sistema de puntos, se utilizó para alentar a los estudiantes a mejorar su fluidez participando en clase en inglés, evitando el español. Cuando terminó el curso, un cuestionario examinó sus percepciones del sistema y cómo afectó su uso del inglés en clase. Resultados. Nuestros resultados indicaron un alto porcentaje de estudiantes, 81%, que evaluaron positivamente el sistema en general y que querrían continuarlo en el futuro, aunque se observaron niveles más bajos de acuerdo en cuanto a la comodidad y el disfrute. Finalmente, los resultados cualitativos hacen eco de estos datos al tiempo que ofrecen más matices sobre cómo el sistema afecta a los estudiantes de WTC. Conclusiones: Concluimos que el sistema fue positivo para las percepciones de los estudiantes sobre su WTC, a pesar de ser una motivación instrumental que mira hacia una orientación más extrínseca. Originalidad. Nuestro trabajo explora el valor de un sistema de refuerzo positivo que puede empujar a los estudiantes a ser más activos en el uso de la lengua extranjera en clase y explora un área poco estudiada en la enseñanza de lenguas extranjeras, la motivación instrumental para mejorar la disposición de los estudiantes a comunicarse.